Autism Spectrum Disorders - in Search of Mechanistic Biomarkers - N. Rabbani; P.J. Thornalley (Moscow State University of Psychology and Education, 2019)
Autism spectrum disorders are a group of neuropsychiatric conditions of increasing prevalence. They are initially detected in early development of children. Diagnosis is currently made on the basis of clinical behaviour and cognition. Improvements in accuracy, timeliness and access to diagnosis to help manage the condition is high on the agenda of the autistic communities. A blood test may help for early-stage detection of autism spectrum disorders to focus support where required - particularly when symptoms are most challenging. This article discusses briefly the scientific basis of diagnosis of autism spectrum disorders and recent emergence of candidate blood tests for autism. We conclude that further validation and improvements in understanding of autism spectrum disorders are required to provide the scientific basis and classifier characteristics for accurate and reliable diagnosis by clinical chemistry blood test.